An in vitro study of pressure increases during contrast injections in diagnostic cerebral angiography. Issue 5 (October 2021) - Marfoglio, Samantha; Kovarovic, Brandon; Hou, Wei; Fiorella, David J; Sadasivan, Chander
Background: During diagnostic cerebral angiography, the contrast bolus injected into a vessel can cause substantial changes in baseline pressures and flows. One potential, and serious complication is the re-rupture of aneurysms due to these injections. The goals of this in vitro study were to evaluate the effect of injection conditions on intraneurysmal pressure changes during angiography. Methods: A silicone replica of a complete circle of Willis model with ophthalmic, anterior communicating, and basilar tip aneurysms was connected to a physiologically accurate flow pump. Contrast injections were performed under different conditions (carotid or vertebral vessel imaging, catheter diameter, injection rate, injection time, and arterial blood flow rate) and the pressure in each aneurysm was recorded before and during each injection. The effect of injection conditions on percentage increase in aneurysm pressures was statistically assessed. Additionally, the effect of the distance between the aneurysm and the catheter-tip on aneurysmal pressures was assessed. Results: Mean intraneurysmal pressures during injection (84.5 ± 10.8 mmHg) were significantly higher than pre-injection pressures (80.4 ± 10.6 mmHg, p < 0.0001). Only 3 of the 5 conditions – carotid injections, higher injection rates, and smaller catheter diameters – significantly increased intraneurysmal pressures. The catheter-tip distance showed no correlation to pressure increases. Conclusions: Increasing contrast injection rates and decreasing catheter diameters are correlated to intraneurysmal pressure increases during angiography irrespective of the distance to the catheter tip. Future in vivo studies are required to confirm these findings and determine whether the amplitude of pressure increases with commonly used injection rates can be clinically detrimental.